Editorial: yoga for QoL in ulcerative colitis—any better than other supportive activities? Authors' reply. Issue 2 (15th June 2017) - Cramer, H.; Dobos, G.; Langhorst, J.
Abstract : Linked Content This article is linked to Andrews and Cramer et al papers. To view these articles visithttps://doi.org/10.1111/apt.14115 andhttps://doi.org/10.1111/apt.14062 .